Egypt - Positive Results from Knowledge Sharing and Modest Lending : An IEG Country Assistance Evaluation 1999-2007 - Independent Evaluation Group (Washington, DC: World Bank, 2013)
This country assistance evaluation reviews World Bank support to the Arab Republic of Egypt from fiscal 1999 through 2007. Egypt's economic performance over the period improved substantially. This was particularly true after 2004, following improvements in economic management, an increase in the pace of structural reforms, and correction of the exchange rate. Gross domestic product growth averaged about five percent over the period, rising to almost seven percent in 2006 and 2007. Human development indicators improved significantly. However, progress in poverty reduction has been disappointing, with a deterioration in the poverty headcount, particularly in Upper Egypt. Future Bank strategy needs to reflect Egypt's middle-income status by including a flexible lending program and an emphasis on knowledge services, including reimbursable technical assistance. The Bank can further strengthen the partnership by focusing on: (i) the persistent issue of poverty and inequality; (ii) analytic work on macroeconomic analysis and income disparities and its improved dissemination; (iii) further financial sector reforms and promoting continued reforms in systems that indirectly combat corruption; and (iv) sectoral strategies and policy and institutional reforms in infrastructure and energy.